Issue of Integrity of Art Education in the Context of Changes in Art and Visual Culture - Musneckienė, Edita (Pedagogika, 2014)
This article examines a paradigmatic change of contemporary art education in the context of visual culture and focus to the integrity of arts in formal and informal art education. The article is based on an international research “Contemporary art and visual culture in education” which reveals the problematic aspects of contemporary arts and visual culture in education in general. The research method was the discourse analysis of the participants and researchers, who presented the insights in reflective groups and during the interview with teachers and educators. This paper explores how contemporary cultural context and the spread of visual culture provide preconditions for changes in art education. The aim of the article is to analyze the problems and perspectives of integral arts education in formal and non-formal education: what the educational challenges and opportunities appear in the context of contemporary art and visual culture? How the integral arts could be realized in art education practice in different arts disciplines and areas of education? Contemporary art and visual culture is increasingly multidimensional, the wide range of visual art forms integral with per formative arts, new technologies and media merge the limits between the arts disciplines. That becomes relevant pedagogical problem with the fact that arts education is traditionally allocated to the separate arts subjects such as music, art, theatre, dance, which also can also be divided into separate areas. This subject segregation of the school curriculum and strong subject orientation limits multimodal contemporary arts education. Secondary Education programs provide opportunities for several options of arts education disciplines (photography, cinema art, graphic design, contemporary music technologies), but it needs special resources for the schools and professional teachers. Many schools follow on traditional model of teaching art and still focusing on simple interpretation of modern artworks, different media and technical skills. Contemporary model of teaching integrated arts and visual culture in education is challenging, because it is based on visual literacy and critical thinking skills, it emphasizes inquiry-based education, a critical understanding of contemporary art practices, problem solving and creating new valuable ideas. Knowledge and experiences came from various sources: formal, non-formal, accidental, individual. Great potential for contemporary art education has non-formal art education programs and projects. Successful project-based initiatives in art education have been excellent examples of arts integration.Artists and other creative people involved into a process of education, their collaboration with schools and communities could initiate some interdisciplinary and collaborative practices. Non-formal arts education environment creates more space for creativity, freedom and diversity. Additional arts education programs, museum and gallery education, artistic competitions and international projects allows for the wider development of arts education. Art education in the new age requires changing attitudes towards learning and teaching, changing roles of the educator and new learning environments.